Penerapan Model Number Head Together (NHT) Dalam Meningkatkan Pemahaman Nilai-Nilai Ideologi Pancasila Tahun Pelajaran 2022/2023 - Nopel Pran (International Forum of Researchers and Lecturers, 2023)
The lack of literacy regarding the values ​​of the Pancasila ideology causes students' understanding to be low, this is proven by the students' scores being still below the KKTP, namely 75. Then also when interacting in class, some students say things that are impolite, make fun of each other, dress some less neatly, and less orderly. Besides that, the way of learning is monotonous and lacks enthusiasm. Then learning is less varied. This research aims 1). Knowing the teacher's activities in implementing the number heads together type Cooperative learning model in increasing students' understanding of the values ​​of the Pancasila ideology. 2). find out students' activities in implementing the number heads together type cooperative learning model in increasing understanding of the values ​​of Pancasila ideology 3). Find out the results of implementing the number heads together type cooperative planning model in increasing understanding of the values ​​of the Pancasila ideology. The research method used is classroom action research. Data collection uses observation and also written tests. The subjects of this research were PAI teachers and 12 students. The results of this research are as follows: 1). The teacher's activities in implementing the Number Head Together (NHT) learning model in class V of SDN 2 Tumbang Kalang were declared successful. This statement is in accordance with the observation results of almost all of the 21 learning process items being implemented. Likewise, the model applied from the six five learning steps has been fulfilled. 2). Students' activities in applying the Number Head Together (NHT) learning model in class V of SDN 2 Tumbang Kalang can increase in cycle II. This can be seen from the 13 activity items from introduction to conclusion, almost all of which were fulfilled, as well as the model implemented, almost all of which were fulfilled. 3). The use of the Number Head Together (NHT) learning model in class V of SDN 2 Tumbang Kalang can increase understanding of the values ​​of the Pancasila ideology in cycle I, namely 66.66% and increase in cycle II to 91.66% with an average class score of 70 in cycle 1 to 78.33 in cycle II